Cadaveric Evaluation of Load to Failure in Canine Gingiva Apposed With Varied Suture Patterns Using Poliglecaprone 25. (March 2021) - Pegg, Jane E.; Rawlinson, Jennifer E.; Kelley, Jennifer L.; Monnet, Eric
The purpose of the study was to determine the effect of suture pattern and repair length on the load to failure in an ex vivo canine gingival model. Healthy mandibular gingiva and mucosa were harvested from fresh cadavers euthanized for purposes unrelated to the study. Samples were randomly assigned by length and pattern. Lingual and buccal free gingival margins were apposed using a simple interrupted (SI), cruciate (XT), simple continuous (SC), or unidirectional knotless continuous barbed suture (SF) closure technique with USP 4-0 poliglecaprone 25 i, ii applied over 2 lengths (3 cm and 6 cm). A custom template was used to ensure uniform suture bite application. Surgical time was recorded. Using a soft tissue mechanical testing frame, samples were tensioned to failure. Testing was video recorded and reviewed in conjunction with the tension trace data for tension at initial failure (Tfail ) and maximum tension sustained (Tmax ). Two factor ANOVA by length and pattern was performed followed by individual one way T-tests. Statistically significant findings were XT-SC-SF patterns were quicker to perform than SI. SF was more likely to fail by suture breakage than tissue tearing, and SF withstood less tension at the 3 cm length than SI-XT-SC. No significant difference was detected in Tmax or Tfail between SI and SC or XT. The study demonstrates that SC and XT are comparable to SI in tension resistance and faster to perform suggesting that SC and XT could replace SI for extraction site closure although further in vivo testing is required.